Strategi Guru PIAUD dalam Membangun Karakter Religius Anak Usia Dini di Era Society 5.0" - Lina Mayasari; Putri Utami Daulay; Yatriany Harahap; Sarmadan Albar; Imron Pulungan (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The background of this research is based on the importance of religious character education from an early age as a moral and spiritual foundation, in accordance with the mandate of Law Number 20 of 2003 concerning the National Education System and Permendikbud Number 137 of 2014 concerning National Standards for Early Childhood Education. This study aims to describe the strategies of Early Childhood Islamic Education (PIAUD) teachers in shaping the religious character of young children in the Society 5.0 era. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation of PAUD teachers. Data analysis follows the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing, with validity testing using source and method triangulation. The research results indicate that teachers' strategies include (1) setting an example, such as greeting others, praying before and after activities, speaking politely, and dressing according to Islamic law; (2) habit formation, such as praying before meals, reciting prayers before and after learning, and performing congregational dhuha prayers; and (3) reinforcing religious values in learning through storytelling and the use of religious songs. These strategies are effective in fostering consistent religious behavior in children, are relevant to learning needs in the Society 5.0 era, and can be adapted in both school and home environments.